Hemorrhage risk and clinical features of multiple intracranial arteriovenous malformations. (January 2016) - Boone, Christine E.; Caplan, Justin M.; Yang, Wuyang; Ye, Xiaobu; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Huang, Judy
Highlights: The natural history and ideal management for multiple arteriovenous malformations (MAVM) remain undetermined. The overall annual hemorrhage incidence rate is 6.7% for MAVM patients. The two most common presenting symptoms are neurological deficit and hemorrhage. Combined treatment modalities have become the most common management strategy. Nidal instability with staged or incomplete treatment requires close monitoring. Abstract: The aim of this report is to examine clinical characteristics, treatment strategies, and annual hemorrhage incidence rate for patients with multiple arteriovenous malformations (MAVM). The PubMed and EMBASE databases and the arteriovenous malformations (AVM) database at The Johns Hopkins Hospital were searched to identify patients with MAVM. Data related to demographics, clinical features, management, and treatment outcomes were analyzed with descriptive statistics. Thirty-eight patients met the inclusion criteria. The annual hemorrhage incidence rate was 6.7%. Surgical intervention remained the most common single-modality treatment from 1949–2011. Between 1990 and 2011, multiple-modality treatment strategies (36% of cases) were employed more frequently. The most common presenting features were neurological deficit (74%) and hemorrhage (63%). In patients undergoing staged treatment of MAVM, hemorrhage of an untreated nidus (n = 5), visualization of a new nidus (n = 9), and disappearance of an untreated nidus (n = 2) were observed. Limitations of this study include small sample size and reporting bias. The annual hemorrhage incidence rate for MAVM patients was approximately two- to three-fold greater than the reported annual hemorrhage rates for solitary AVM. Combining different treatment modalities has become the most common management strategy. The potential instability of remaining nidi with staged or incomplete treatment necessitates close follow-up in these cases.